Implementasi Pendidikan Agama Kristen sebagai Media Deradikalisme di Kalangan Remaja - Olive Reny Sekewael (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
Religion holds an important place in individual’s life. Religion can lead individuals or communities to build a peaceful life with others; conversely, it can also contribute to conflict. The Maluku’s context as a region that has experienced ethnicity and religion conflicts, clearly demonstrates these contrasting realities. Religion can serve as a unifying force, yet it can also become a source of fragmentation within religiously diverse societies. Therefore, the cultivation of values such as mutual acceptance and respect must begin at an early age, including during adolescence. Christian Religious Education (CRE) serves as one of the educational media that can be utilized to foster deradicalism attitudes and openness toward adherents of other religions in order to promote peace. This study employs a descriptive qualitative method through interviews conducted in group and questionnaires administered to students and teachers at SMA Kristen Rehoboth Ambon. The findings indicate that Christian values have been effectively instilled through CRE classes. However, the process of applying these values often encounters challenges due to emotional wounds resulting from past conflicts. Consequently, the development of contextualized learning strategies becomes an essential step that must be carefully considered and implemented.